The Effect of Service Quality, Infrastructure, and Hospital Image on Patient Satisfaction in Pharmaceutical Services at the Outpatient Pharmacy Depot of RSUD Dr. Harjono Ponorogo - Setyawan, Ari Bambang; Setyawan, Anton Agus; Romadhon, Yusuf Alam (Publikasi Indonesia, 2025)
This study aims to analyze the effect of service quality, infrastructure, and hospital image on patient satisfaction in pharmaceutical services at the outpatient pharmacy depot of RSUD Dr. Harjono Ponorogo. The research method used is quantitative correlational research with a descriptive quantitative approach. The population consists of 200 patients who purchased medications at the Outpatient Pharmacy Depot of RSUD Dr. Harjono Ponorogo in May 2025, with total sampling technique. Data collection was conducted using questionnaires with a Likert scale. Data analysis techniques included validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results showed that service quality has a positive and significant effect on patient satisfaction (t = 7.230, sig = 0.000), infrastructure has a positive and significant effect on patient satisfaction (t = 6.846, sig = 0.000), and hospital image has a positive and significant effect on patient satisfaction (t = 9.312, sig = 0.000). Simultaneously, service quality, infrastructure, and hospital image have a significant effect on patient satisfaction (F = 187.729, sig = 0.000). The coefficient of determination (Adjusted R²) is 0.738, indicating that 73.8% of patient satisfaction variation is explained by the three independent variables. The study concludes that improving service quality, infrastructure, and hospital image is crucial for enhancing patient satisfaction in pharmaceutical services.